Oncology and cardiology positron emission tomography/computed tomography faced with COVID-19: A review of available literature data - Minamimoto, Ryogo (Frontiers in Medicine, 2022)
The COVID-19 pandemic has forced people to significantly change their lifestyles and attitudes, and has greatly burdened healthcare delivery systems worldwide. The redistribution of the medical delivery system to maintain normal medical care while responding generously to COVID-19 is a continuing challenge that weighs heavily on medical institutions. Among imaging modalities, chest X-rays and CT examinations have clearly made a large contribution to treatment of COVID-19. In contrast, it is difficult to express the standpoint of nuclear medicine examinations in a straightforward manner, as the greatest emphasis in this modality has been on how necessary medical care can continue to be provided. Many clinical reports of nuclear medicine examinations related to COVID-19 have been published, and knowledge continues to accumulate. This review provides a summary of the current state of oncology and cardiology positron emission tomography (PET) examinations related to COVID-19, and includes preparation of the nuclear medicine department, trends in PET examinations, specific imaging findings on 18F-fluorodeoxyglucose (FDG) PET/CT, imaging of complications of COVID-19, PET tracers other than FDG, and the effects of vaccines on PET imaging findings.